2003
DOI: 10.1557/proc-806-mm8.11
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Ti-Based, Dendrite/Nanostructured-Matrix Composites

Abstract: Electron microscopy of the composite-forming alloys Ti 60 Cu 14 Ni 12 Sn 4 Nb 10 and Ti 60 Cu 14 Ni 12 Sn 4 Ta 10 , shows that for both alloys, the microstructure consists of an array of micron-scale dendrites surrounded by a nanoscale binary eutectic. In the Ta-containing alloy, one of the eutectic phases has been identified as having a bcc crystal structure similar to that of the dendrites. In the Nb-containing alloy, one of the eutectic phases has been found to have a similar composition to that of the dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Dai et al [17] It was again shown that the matrix consisted of a binary eutectic and the earlier proposal that one of the eutectic phases had the same crystal structure as the dendrites [18] was confirmed by selected area electron diffraction (SAD). [17] The contribution from the two eutectic phases could not be separated using SAD and so the diffraction patterns obtained showed two sets of spots superimposed.…”
Section: Microstructural Characterisation and Phase Formationmentioning
confidence: 91%
“…Dai et al [17] It was again shown that the matrix consisted of a binary eutectic and the earlier proposal that one of the eutectic phases had the same crystal structure as the dendrites [18] was confirmed by selected area electron diffraction (SAD). [17] The contribution from the two eutectic phases could not be separated using SAD and so the diffraction patterns obtained showed two sets of spots superimposed.…”
Section: Microstructural Characterisation and Phase Formationmentioning
confidence: 91%